2012
DOI: 10.1002/pola.26091
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of gradient copolymers with simultaneously tailor‐made chain composition distribution and glass transition temperature by semibatch ATRP: From modeling to application

Abstract: Recent studies have demonstrated that gradient copolymers exhibit unique thermal properties. Although these properties can be determined by copolymer composition, other factors such as chain and sequence lengths and their distributions can also influence them. Accordingly, the synthesis of gradient copolymers requires simultaneously tailor-made chain structure and thermal properties. In this work, we carried out a systematic study on the preparation of poly(methyl methacrylate-grad-2-hydroxyethyl methacrylate)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
67
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 63 publications
(73 citation statements)
references
References 72 publications
2
67
0
1
Order By: Relevance
“…2431 Moreover, ATRP can control copolymer composition (e.g., block and gradient copolymers), topology (e.g., stars and bottlebrushes), and location of functional groups (e.g., α -, ω -, or both, periphery or core functional stars, and side-group functional brushes). 3237 A wide range of monomers is available for ATRP, including (meth)acrylates, styrenes, acrylamides, acrylonitrile, and methacrylic acid. 3842 …”
Section: Introductionmentioning
confidence: 99%
“…2431 Moreover, ATRP can control copolymer composition (e.g., block and gradient copolymers), topology (e.g., stars and bottlebrushes), and location of functional groups (e.g., α -, ω -, or both, periphery or core functional stars, and side-group functional brushes). 3237 A wide range of monomers is available for ATRP, including (meth)acrylates, styrenes, acrylamides, acrylonitrile, and methacrylic acid. 3842 …”
Section: Introductionmentioning
confidence: 99%
“…a comparison of the tensile curves between CNF nanopapers and the nanocomposites at35 and 50 wt% of polymer content, respectively. Furthermore, we calculate the work of fracture or toughness (U t ) from the area under the tensile σ-ε curves for all compositions(Figure 5c).While the relationship between U t and polymer content for an individual set of nanopapers for one copolymer is fairly linear (orange-red vertical gradient), the overall trend inverts upon incorporation of EG units and when going from high to low T g .…”
mentioning
confidence: 99%
“…To date, most gradient sequence copolymers have been synthesized from vinyl-containing monomers (37)(38)(39)(40). These reports have demonstrated that the gradient sequence materials exhibit unique properties compared to their block, random and alternating counterparts.…”
Section: Scheme 1 Copolymer Sequencesmentioning
confidence: 98%